Pendekatan Etika Teleologi dalam Pengambilan Keputusan Tindak Aborsi - Sa'adah, Annas Fitria (Program Studi Filsafat Agama Hindu IAHN Gde Pudja Mataram, 2024)
Abortion is the removal of a living fetus from a mother's womb through human intervention before birth by killing her. This abortion phenomenon certainly has many pros and cons, especially regarding ethics. The aim of this research is to look at abortion decision making from a teleological ethical perspective. The form of this research is qualitative, with the research method being a library research study. The material object of this research is abortion and the formal object is teleological ethics. The methodology used is interpretation, description, verstehen, heuristics, hermeneutics, reflection. The results of this research provide an overview of teleological ethics in making decisions about abortion, namely as long as the abortion produces the desired happiness, the action is permissible. Abortion based on teleological ethics is permitted for medical reasons, but apart from medical reasons, abortion should not be carried out.